Youth in the Age of Hatred: Religious and Ethnic Factors Within the Islamic Senior High School Students’ Reception Toward Hate Narratives - Ahmad Aminuddin; M. Iqbal Ahnaf (Graduate Program of Pontianak Institute of Islamic Studies, 2019)
The rise of hate narratives along with the new model of communication through the internet has become a new challenge for people in this digital era, especially for youth, the Z generation. This generation, in fact, has an intimacy with the internet. It means that they have more possibility for the influence of hate narratives. This study is aimed exploring the influential factors on Z generation reception to the hate narratives on the internet. Specifically, it proposes to recognize the influential factors on the reception of the students of Madrasah Aliyah Negri (MAN) or State Islamic Senior High School of Tuban (MAN Tuban), East Java. This work is based on two hate narrative issues of Suku, Agama, Ras dan Antargolongan (SARA) or religious, ethnic and intergroup diversity backgrounds, including those of anti-Christianity and those anti-Shiite. This work concludes that the influential factors to the students' reception toward hate narratives come from two categories. First, students are to be the audience of their social systems and backgrounds. The involvement of the students in fundamentalist Muslim groups, in fact, has led them to have exclusive views in seeing others and to feel always under intergroup contestation. Second, the role of the characters of the narratives that influence student’s thought is very important to count. It includes the legitimization through emotion which specifically presents fear and feeling threatened. Those characters have further triggered the students’ empathy to do something beneficial for the sake of the in-group (altruism). In addition, the characters of the narratives have the figures behind them that have influenced students to immediately believe in the narratives they offer only through seeing their profiles on the internet showing their expertise.